Impact-resistant hybrid fiber UHPC for bridge expansion device anchor and characterization method of its impact fatigue performance

By using impact-resistant mixed fiber UHPC in the anchor of the bridge expansion device and establishing an impact durability life prediction formula, the problem that the life of the bridge expansion joint anchor cannot be pre-characterized, achieving a longer service life and lower maintenance frequency.

CN118706648BActive Publication Date: 2025-03-18GUANGXI UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410715168.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2025-03-18
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

The lifespan of the bridge expansion joint anchor cannot be effectively pre-characterized, resulting in frequent maintenance and traffic interference.

Method used

Impact-resistant mixed fiber ultra-high performance concrete (UHPC) is used to establish an impact durability life prediction formula by reasonably taking the total fiber dosage and substitution rate to evaluate the impact fatigue performance of the anchors of the bridge expansion device.

Benefits of technology

It significantly improves the impact resistance of the anchor body of the bridge telescopic device, extends its service life, reduces maintenance frequency, and reduces traffic interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118706648B_ABST
    Figure CN118706648B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of bridges, and discloses a method and system for characterizing the impact fatigue performance of an anchor body of a bridge expansion device. The construction performance, basic mechanical properties and repeated drop hammer impact performance tests at different impact heights of UHPC, plain UHPC, and C50 steel fiber concrete (steel fiber content 1%) with a total fiber content of 2% and four synthetic fiber replacement rates of PVA, PP, PE, and POM of 0%, 10%, 20%, and 30% respectively are carried out; the influence of different synthetic fiber types and volume replacement rates on the construction performance, basic mechanical properties and impact resistance of UHPC is revealed; the internal relationship of characteristic impact numbers of different impact heights of various proportions is analyzed; and the relationship between the impact resistance of UHPC, hybrid fiber UHPC, plain UHPC, and C50 steel fiber concrete is compared. A method for characterizing the impact fatigue performance of an anchor body of a bridge expansion device, key parameters of UHPC of impact-resistant hybrid fibers of an anchor body of a bridge expansion device, and a prediction formula for the impact durability life of UHPC under the key parameters are proposed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of bridges, and in particular relates to an impact-resistant UHPC anchor body of a bridge expansion device and a method and system for characterizing its impact fatigue performance. Background Art

[0002] As an important bridge facility, bridge expansion joints bear the impact of wheel loads for a long time, and their durability faces severe challenges. According to statistics, expansion joints account for less than 1% of the total cost of bridges, but they account for 16% of bridge damage, and the maintenance costs incurred during the operation period reach more than 20% of the total maintenance costs of bridges. Therefore, it is of great significance to ensure that expansion joints are strong, durable and function properly.

[0003] Fatigue cracking or damage of concrete anchors is the main disease problem faced by expansion joints. After testing more than 800 bridges in a certain province, it was found that 24.6% of the bridge expansion joints had concrete anchor damage. Even if C50 steel fiber concrete is used, it is still easy to crack and break, and needs to be replaced every 5 to 8 years. Therefore, improving the strength and impact toughness of the expansion joint cement-based composite anchor has become the key to extending the life of highway bridge expansion joint devices.

[0004] Ultra-high performance concrete (UHPC) has excellent mechanical properties and durability, and has broad application prospects in structures subjected to impact loads. However, the share of steel fiber in the cost of UHPC increases with the increase in the amount of steel fiber added. When only 2% (volume) of steel fiber is added, the fiber cost exceeds the cost of the UHPC matrix. If part of the steel fiber is replaced with the same volume of synthetic fiber, reasonably mixed, and complementary advantages, the deformation performance, toughness and impact resistance of UHPC can be significantly improved, and the cost can be appropriately reduced. If these performance requirements remain unchanged, the total fiber content can be reduced, further reducing the cost.

[0005] The prior art has conducted a drop hammer impact test on hybrid fiber UHPC, but since the changes in parameters such as the test height and the replacement rate have not been systematically designed, and there is a lack of comparison with the drop hammer impact test results of C50 steel fiber concrete used in actual bridge expansion joint anchors for many years, the objective laws involved in the present invention could not be discovered and the present invention could not be proposed.

[0006] The prior art uses hybrid fiber UHPC in bridge expansion joint anchors, but only examines the effects of PVA and PP replacing part of the steel fibers (the replacement rate is 16.67%) on compressive strength, flexural strength and thermal crack resistance, let alone discovering the objective laws involved in the present invention and proposing the present invention.

[0007] The free-fall hammer impact test of the existing technology adopts the "Fiber Concrete Test Method" (CECS13:2009) and the American Concrete Institute (ACI 544.2R-89) for the evaluation criteria of the specimen impact performance. Both of them are based on the specimen failure (main crack width greater than 15mm) and the number of impacts of the initial crack as the evaluation criteria, but it is not suitable for the characteristics of bridge expansion joint anchor bodies that can work with cracks as long as the crack width does not exceed the maximum crack width limit of reinforced concrete (0.10mm~0.20mm).

[0008] Through the above analysis, the problems and defects of the prior art are as follows:

[0009] (1) The service life of bridge expansion joint anchors for more than several years cannot be characterized in advance.

[0010] (2) The service life of expansion joint anchors is far below or lower than the design reference period of the bridge, requiring multiple or repeated repairs, which causes great interference to traffic. Summary of the invention

[0011] In view of the problems existing in the prior art, the present invention provides an anchor body of a bridge expansion device and a method for characterizing impact fatigue performance.

[0012] The present invention is implemented in this way: a bridge expansion device anchor body and impact fatigue performance characterization method comprising:

[0013] Step 1, experimental testing and characterization of impact life determination of cement-based composite anchors of bridge expansion joints;

[0014] Step 2, reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC;

[0015] Step 3, impact durability life prediction formula for impact-resistant hybrid fiber UHPC.

[0016] Furthermore, the reasonable value determination method of the key parameters of the impact-resistant hybrid fiber UHPC is as follows:

[0017] The key parameters of the impact-resistant hybrid fiber UHPC of the anchor body of the bridge expansion device include: the total fiber volume dosage is 2%±0.5%; the replacement rate of synthetic fibers (polyvinyl alcohol fiber PVA, polypropylene fiber PP, polyethylene fiber PE, polyoxymethylene fiber POM) for steel fibers is 8%~16%; the length of steel fiber is 8mm~16mm, and the aspect ratio is 60~100; the length of PVA, PP, PE, and POM are all about 10~14mm, the aspect ratio of the former three is 300~500, and the aspect ratio of the latter is 60~100, the aggregate diameter of UHPC does not exceed 3mm, the compressive strength of UHPC is not less than 120MPa, and the tensile strength is not less than 7MPa.

[0018] Furthermore, the impact durability life prediction formula of the impact-resistant hybrid fiber UHPC is:

[0019] When the total fiber content is 2% ± 0.5%, the substitution rate of the four synthetic fibers PVA, PP, PE, and POM does not exceed 30%, and the impact height is 45 to 75 cm, the number of impacts of the durable crack width of UHPC with different mixed fibers and impact heights can be calculated according to the following formula:

[0020]

[0021] Among them, b2 and c2 are coefficients related to fiber characteristic parameters;

[0022] b2=6.20-1.39λ sf -0.08λ pf (2)

[0023] c2=(5.35-3.85λ sf +13.46λ pf -15.41λ pf 2 +5.54λ pf 3 )·10 11 (3)

[0024] Where: Steel fiber characteristic parameter λ sf , Synthetic fiber (PVA, PP, PE, POM) characteristic parameters λ pf Calculate as follows:

[0025] λ sf =ρ sf l sf / d sf (4)

[0026] λ pf =ρ pf l pf / d pf (5)

[0027] In the above formula (2), ρ sf , pf are the volumetric dosages of steel fiber and synthetic fiber, respectively, in percentage; l sf / d sf With l pf / d pf are the aspect ratios of steel fiber and synthetic fiber respectively;

[0028] According to the relevant parameters of the mixed fiber UHPC and formula (1), the durable crack width impact number of the UHPC at an impact height of 50 cm is calculated, and the predicted impact fatigue life is obtained by dividing it by 20.

[0029] Another object of the present invention is to provide an impact fatigue performance characterization system for an anchor body of a bridge expansion device, comprising:

[0030] Life determination module, used for experimental testing and characterization of impact life determination of cement-based composite anchors in bridge expansion joints;

[0031] The value module is used to reasonably determine the key parameters of impact-resistant hybrid fiber UHPC;

[0032] Life prediction module, used for the impact durability life prediction formula of impact-resistant hybrid fiber UHPC.

[0033] Another object of the present invention is to provide a computer device, which includes a memory and a processor, wherein the memory stores a computer program, and when the computer program is executed by the processor, the processor executes the steps of the method for characterizing the impact fatigue performance of the anchor body of the bridge expansion device.

[0034] Another object of the present invention is to provide a computer-readable storage medium storing a computer program, which, when executed by a processor, enables the processor to execute the steps of the method for characterizing the impact fatigue performance of the anchor body of the bridge expansion device.

[0035] Another object of the present invention is to provide an information data processing terminal, which is used to implement an impact fatigue performance characterization system for the anchor body of the bridge expansion device.

[0036] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0037] First, the present invention aims at the problem that the service life of the anchor concrete of bridge expansion joint is far lower than the design reference period of the bridge and the impact resistance of the concrete in the anchoring area lacks reasonable characterization. The present invention conducts construction performance, basic mechanical properties and repeated drop hammer impact performance tests at different impact heights of UHPC, plain UHPC and C50 steel fiber concrete (steel fiber content 1%) with a total fiber content of 2% and four synthetic fiber replacement rates of PVA, PP, PE and POM of 0%, 10%, 20% and 30% respectively; reveals the influence of different synthetic fiber types and volume replacement rates on the construction performance, basic mechanical properties and impact resistance of UHPC; analyzes the inherent relationship of the characteristic impact number of different impact heights of each ratio; compares the impact resistance of UHPC, hybrid fiber UHPC, plain UHPC and C50 steel fiber concrete. The present invention proposes a characterization method for the impact fatigue performance of the anchor of the bridge expansion device, the key parameters of the impact-resistant hybrid fiber UHPC of the anchor of the bridge expansion device, and the prediction formula of the impact durability life of UHPC under the key parameters.

[0038] The present invention overcomes the shortcoming that the service life of the bridge expansion joint anchor body of more than several years cannot be characterized in advance, avoids the problem that the service life of the expansion joint anchor body is far lower than or lower than the design reference period of the bridge, requires multiple or repeated maintenance, and causes great interference to traffic, and facilitates obtaining the key parameters of the UHPC mixed fiber according to the service life requirements.

[0039] (1) Based on the service life of concrete in the anchorage area of ​​bridge expansion joints and the corrosion conditions of steel wire in concrete, the concept of durable crack width impact number was proposed; based on the result that the durable crack width impact number of C50 steel fiber concrete at an impact height of 50 cm is much smaller than the number of times the bridge expansion joints are subjected to wheel action during their service life, and the fact that the minimum impact height of the standard impact test is 47.5 cm and is very close to 50 cm, and the test workload (number of impacts) should not be too large, a reasonable method for characterizing the impact resistance of concrete in the anchorage area of ​​expansion joints was proposed - using the durable crack width impact number at an impact height of 50 cm in the standard impact test.

[0040] (2) Regardless of which synthetic fiber, PVA, PE, PP, or POM, replaces part of the steel fiber, the total fiber content remains unchanged at 2%, and the characteristic impact number and toughness coefficient of the mixed fiber UHPC are the largest when the synthetic fiber substitution rate is 10% (i.e., the dosage is 0.2%); when the synthetic fiber substitution rate exceeds 10%, as the substitution rate increases, the impact resistance of the PVA mixed fiber UHPC decreases slowly, while the other three mixed fiber UHPC decreases rapidly, which shows the importance of controlling the substitution rate of each synthetic fiber.

[0041] (3) When the crack width is less than 0.5 mm, the crack width of all UHPC specimens increases slowly with the increase of the impact number. When the crack width is greater than 1.0 mm, it increases rapidly with the impact number. When the impact height is 50 cm, the growth rate of the crack width with the impact number is significantly lower than that when the impact height is 100 cm. The growth rate of the crack width of C50 fiber concrete with the impact number is much greater than that of hybrid fiber UHPC.

[0042] (4) According to the proposed characterization method of the impact resistance of the expansion joint anchorage area, the life of the C50 steel fiber concrete bridge expansion joint anchorage area is 5 years, and the life of the bridge expansion joint anchorage area of ​​the mixed fiber UHPC with a replacement rate of 10% for PP, PE, PVA, and POM is 299.5, 268.5, 264.0, and 163.5 years, respectively, and the life of the steel fiber UHPC and C50 PP fiber concrete is 70.4 and 2.6 years, respectively. According to the inference, the actual life of the first five is longer than the aforementioned, and the actual life of the latter is shorter than the aforementioned.

[0043] (5) The calculation formulas for the initial crack impact number N1, the durable crack width impact number N2 and the destruction impact number N3 of UHPC based on the fiber characteristic parameters and the impact height were proposed. When the total fiber content was 2%, the substitution rate of the four synthetic fibers, PVA, PP, PE and POM, did not exceed 30%, and the impact height was not greater than 75 cm, the prediction accuracy was high enough to meet the engineering accuracy requirements. However, the prediction accuracy decreased rapidly with the increase of the impact height.

[0044] Second, the expected benefits and commercial value of the technical solution of the present invention after transformation are: it overcomes the deficiency that the service life of the bridge expansion joint anchor body for more than several years cannot be pre-characterized, avoids the problem that the service life of the expansion joint anchor body is far lower than or lower than the design reference period of the bridge, requires multiple or repeated repairs, and interferes with traffic, and facilitates obtaining the key parameters of the UHPC mixed fiber according to the service life requirements. The invented hybrid fiber UHPC does not need to be repaired during the 100-year design reference period of the bridge, while the service life of the traditional concrete anchor body is only 5-8 years, that is, it needs to be renovated 11.5-19 times during the design reference period. Assuming that the invention is applied to 100,000 km nationwide, with an average of 1 telescopic anchor per kilometer, 5 days of traffic interruption for each renovation, 8,000 vehicles / (road.day), 0.5 yuan per kilometer, and 50,000 yuan for the renovation of one expansion joint, the toll loss caused by this during the design reference period is at least 0.5 yuan / (km.travel)*8,000 vehicles / day*5 days*100,000 (km)*11.5 times=230 billion yuan, and the labor and material costs are at least 50,000 yuan*100,000*11.5=57.5 billion, and the one-time investment increases the labor and material costs by a maximum of 30,000 yuan / road, so the increase in labor and material costs does not exceed 3 billion. In summary, the direct economic benefits of the additional 3 billion investment are 2300+575=287.5 billion, which is a huge direct economic benefit. The social benefits are even more immeasurable.

[0045] The technical solution of the present invention fills the technical gaps in the industry at home and abroad: for the first time, it solves the technical gap that there is no reasonable characterization of the life of expansion joint anchor bodies; for the first time, reasonable parameters of hybrid fiber UHPC with an impact life of 32.7 times or more of the impact life of traditional C50 steel fiber concrete are given; and it fills the technical gap that there is no reasonable prediction method for the number of impacts on the durable crack width of hybrid fiber UHPC expansion joint anchor bodies.

[0046] The technical solution of the present invention solves the technical problems that people have been eager to solve but have never succeeded in solving: the good service life of the concrete of the bridge expansion joint anchor is far lower than the design reference period of the bridge and the impact resistance of the concrete in the anchoring area lacks reasonable characterization.

[0047] The technical solution of the present invention overcomes technical prejudice: for the first time, the durable crack width impact number is used to characterize the impact resistance life of the concrete anchor of the bridge expansion joint, which reflects the essential characteristics of the use of the bridge and overcomes the technical prejudice of the traditional method of using the initial crack impact number and the destructive impact number to characterize the impact resistance life.

[0048] Third, the present invention provides an innovative method for characterizing the impact fatigue performance of the anchor of the bridge expansion joint, which first focuses on the impact resistance life of the cement-based composite anchor of the bridge expansion joint. In bridge engineering, the expansion joint is an indispensable part, and its stability and durability directly affect the overall performance and service life of the bridge. Therefore, through precise experimental testing and characterization, we can accurately evaluate the life of the anchor under impact and provide strong protection for the safe operation of the bridge.

[0049] In step S102, the present invention reasonably selects key parameters for impact-resistant hybrid fiber UHPC (ultra-high performance concrete). As a new type of high-performance building material, UHPC has excellent mechanical properties and durability, especially outstanding impact resistance. By carefully selecting key parameters, we can ensure that the application of UHPC in the anchor of the bridge expansion device achieves the best effect and further improves the impact resistance of the bridge.

[0050] In step S103, the present invention establishes a prediction formula for the impact durability life of impact-resistant hybrid fiber UHPC. This formula is established based on a large amount of experimental data and theoretical analysis, and can accurately predict the impact durability life of the anchor body during long-term use. This not only provides a scientific basis for the design and maintenance of bridges, but also lays a solid foundation for the technological progress of future bridge engineering.

[0051] The impact fatigue performance characterization method of the anchor body of the bridge expansion device provided by the present invention solves the problems existing in the prior art and has achieved significant technical progress. Through precise experimental testing, reasonable parameter values ​​and scientific life prediction formulas, we can better evaluate and improve the impact resistance of the anchor body of the bridge expansion device, and provide strong guarantees for the safe operation and long-term use of the bridge. The achievement of this result will bring new opportunities and challenges to the technical development in the field of bridge engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a flow chart of a method for characterizing the impact fatigue performance of an anchor body of a bridge expansion device provided in an embodiment of the present invention.

[0053] Figure 2 It is a structural block diagram of the impact fatigue performance characterization system of the anchor body of the bridge expansion device provided in an embodiment of the present invention.

[0054] Figure 3 2 is a diagram of a test fiber material provided in an embodiment of the present invention.

[0055] Figure 4 2 is a diagram of a drop weight impact test device provided in an embodiment of the present invention.

[0056] Figure 5 Graph showing the effect of synthetic fiber substitution on UHPC expansion provided by an embodiment of the present invention.

[0057] Figure 6 Graph showing the effect of synthetic fiber substitution on the compressive strength of UHPC provided in an embodiment of the present invention.

[0058] Figure 7 Graph showing the effect of synthetic fiber substitution on the flexural strength of UHPC provided in an embodiment of the present invention.

[0059] Figure 8 Graph showing the effect of synthetic fiber substitution on the tensile strength of UHPC provided by an embodiment of the present invention.

[0060] Fig. 9 It is a relationship diagram between the maximum crack width and the impact number of UHPC and fiber concrete at an impact height of 100 cm provided by an embodiment of the present invention.

[0061] Fig.10 It is a relationship diagram between the maximum crack width and the impact number of UHPC and fiber concrete at an impact height of 50 cm provided by an embodiment of the present invention.

[0062] Fig.11 It is a comparison chart of the calculated value and the experimental value of N2 provided in the embodiment of the present invention. DETAILED DESCRIPTION

[0063] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0064] Example 1: Characterization of impact fatigue performance of steel fiber reinforced ultra-high performance concrete (UHPC) anchor

[0065] S101: Prepare UHPC anchor specimens with different steel fiber content (0.5%, 1.0%, 1.5% by volume). Use a drop hammer impact tester to subject the specimens to impact loading with different impact energies (50J, 100J, 150J), and record the impact damage times and crack development of the specimens.

[0066] S102: Analyze the test data to determine the influence of steel fiber content on the impact resistance of UHPC anchor body. Through regression analysis, establish the relationship model between steel fiber content and impact failure times.

[0067] S103: Combining the test results with theoretical analysis, a prediction formula for the impact durability life of steel fiber reinforced UHPC anchors is derived, taking into account factors such as steel fiber content, impact energy, and anchor size.

[0068] Example 2: Characterization of impact fatigue properties of basalt fiber and polypropylene fiber hybrid reinforced UHPC anchor

[0069] S101: Prepare UHPC anchor specimens with different mixed fiber dosages (basalt fiber 0.5% + polypropylene fiber 0.5%, basalt fiber 1.0% + polypropylene fiber 1.0%, basalt fiber 1.5% + polypropylene fiber 1.5% by volume). Use a drop hammer impact tester to load the specimens with different impact energies (50J, 100J, 150J), and record the impact damage times and crack development of the specimens.

[0070] S102: Analyze the test data to determine the influence of the mixed fiber content on the impact resistance of the UHPC anchor body. Through regression analysis, establish a relationship model between the mixed fiber content and the number of impact failures.

[0071] S103: Combining the test results with theoretical analysis, the impact durability life prediction formula of basalt fiber and polypropylene fiber hybrid reinforced UHPC anchor body is derived, considering factors such as hybrid fiber dosage, impact energy, and anchor body size.

[0072] Expected results:

[0073] Through the above two embodiments, the following results can be obtained:

[0074] The effects of different types and dosages of fibers on the impact resistance of UHPC anchors were quantified.

[0075] A relationship model between fiber content and impact failure times was established to provide a reference for the design of UHPC anchor bodies.

[0076] The impact durability life prediction formula of UHPC anchor body was derived, which can be used to evaluate the service life of the anchor body of bridge expansion device in actual service environment.

[0077] Note:

[0078] In actual tests, specimen preparation and test conditions should be strictly controlled to ensure the accuracy and reliability of the test results.

[0079] When deriving the impact durability life prediction formula, various influencing factors should be fully considered, such as fiber type, dosage, impact energy, anchor body size, ambient temperature, etc.

[0080] The method of the present invention can be applied to anchor bodies of different types of bridge expansion devices, and provides technical support for the design and maintenance of bridge expansion devices.

[0081] like Figure 1 As shown, a method for characterizing the impact fatigue performance of an anchor body of a bridge expansion device provided by an embodiment of the present invention comprises the following steps:

[0082] S101, Experimental testing and characterization of impact life determination of cementitious composite anchors in bridge expansion joints;

[0083] S102, reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC;

[0084] S103, impact durability life prediction formula for impact-resistant hybrid fiber UHPC.

[0085] The reasonable value determination method of the key parameters of the impact-resistant hybrid fiber UHPC provided in the embodiment of the present invention is as follows:

[0086] The key parameters of the impact-resistant hybrid fiber UHPC of the anchor body of the bridge expansion device include: the total fiber volume dosage is 2%±0.5%; the replacement rate of synthetic fibers (polyvinyl alcohol fiber PVA, polypropylene fiber PP, polyethylene fiber PE, polyoxymethylene fiber POM) for steel fibers is 8%~16%; the length of steel fiber is 8mm~16mm, and the aspect ratio is 60~100; the length of PVA, PP, PE, and POM are all about 10~14mm, the aspect ratio of the former three is 300~500, and the aspect ratio of the latter is 60~100, the aggregate diameter of UHPC does not exceed 3mm, the compressive strength of UHPC is not less than 120MPa, and the tensile strength is not less than 7MPa.

[0087] The impact durability life prediction formula of the impact-resistant hybrid fiber UHPC provided in the embodiment of the present invention is:

[0088] When the total fiber content is 2% ± 0.5%, the substitution rate of the four synthetic fibers PVA, PP, PE, and POM does not exceed 30%, and the impact height is 45 to 75 cm, the number of impacts of the durable crack width of UHPC with different mixed fibers and impact heights can be calculated according to the following formula:

[0089]

[0090] Among them, b2 and c2 are coefficients related to fiber characteristic parameters;

[0091] b2=6.20-1.39λ sf -0.08λ pf (2)

[0092] c2=(5.35-3.85λ sf+13.46λ pf -15.41λ pf 2 +5.54λ pf 3 )·10 11 (3)

[0093] Where: Steel fiber characteristic parameter λ sf , Synthetic fiber (PVA, PP, PE, POM) characteristic parameters λ pf Calculate as follows:

[0094] λ sf =ρ sf l sf / d sf (4)

[0095] λ pf =ρ pf l pf / d pf (5)

[0096] In the above formula (2), ρ sf , pf are the volumetric dosages of steel fiber and synthetic fiber, respectively, in percentage; l sf / d sf With l pf / d pf are the aspect ratios of steel fiber and synthetic fiber respectively;

[0097] According to the relevant parameters of the mixed fiber UHPC and formula (1), the durable crack width impact number of the UHPC at an impact height of 50 cm is calculated, and the predicted impact fatigue life is obtained by dividing it by 20.

[0098] like Figure 2 As shown, an impact fatigue performance characterization system for an anchor body of a bridge expansion device provided by an embodiment of the present invention includes:

[0099] Life determination module, used for experimental testing and characterization of impact life determination of cement-based composite anchors in bridge expansion joints;

[0100] The value module is used to reasonably determine the key parameters of impact-resistant hybrid fiber UHPC;

[0101] Life prediction module, used for the impact durability life prediction formula of impact-resistant hybrid fiber UHPC.

[0102] Another object of the present invention is to provide a computer device, which includes a memory and a processor, wherein the memory stores a computer program, and when the computer program is executed by the processor, the processor executes the steps of the method for characterizing the impact fatigue performance of the anchor body of the bridge expansion device.

[0103] Another object of the present invention is to provide a computer-readable storage medium storing a computer program, which, when executed by a processor, enables the processor to execute the steps of the method for characterizing the impact fatigue performance of the anchor body of the bridge expansion device.

[0104] Another object of the present invention is to provide an information data processing terminal, which is used to implement an impact fatigue performance characterization system for the anchor body of the bridge expansion device.

[0105] The present invention is specifically implemented:

[0106] I. Technical solutions of inventions

[0107] 1) It is advisable to use the standard impact test method specified in Section 6.16 of "Fiber Concrete Test Method" (CECS13:2009) at an impact height of 50cm (or a certain value within 50cm±10cm) to determine the number of impacts of the durable crack width (the number of impacts when the maximum crack width on the specimen surface reaches a certain value of 0.10mm~0.20mm, which is based on the nature of the bridge (highway bridge or railway bridge), "Durability Design Code for Concrete Structures of Highway Engineering" (JTG / T3310-2019) and "Durability Design Code for Concrete Structures of Railway Engineering" (TB10005-2010 , J1167-2011), the maximum crack width limit of reinforced concrete components determined by the environmental category of the bridge location)" characterizes the impact fatigue performance of the expansion joint anchor (cement-based composite material), and the good service life of the expansion joint C50 steel fiber concrete (steel fiber volume content 1%, the steel fiber is a steel ingot milling pin type with a length of 30mm, a width of 2mm, and a thickness of 0.6mm) can be estimated based on the multiples of the durable crack width impact times (or 100 times for safety) of the expansion joint C50 steel fiber concrete (steel fiber volume content 1%) anchor 5 years.

[0108] 2) The key parameters of the impact-resistant hybrid fiber UHPC anchor body of the bridge expansion device include: the total fiber volume content is 2%±0.5%; the replacement rate of synthetic fibers (polyvinyl alcohol fiber PVA, polypropylene fiber PP, polyethylene fiber PE, polyoxymethylene fiber POM) for steel fibers is 8%~16%; the length of steel fiber is 8mm~16mm, and the aspect ratio is 60~100; the length of PVA, PP, PE, and POM are all about 10~14mm, the aspect ratio of the first three is 300~500., and the aspect ratio of the latter is 60~100. The aggregate diameter of UHPC does not exceed 3mm, the compressive strength of UHPC is not less than 120MPa, and the tensile strength is not less than 7MPa.

[0109] 3) When the total fiber content is 2% ± 0.5%, the substitution rate of the four synthetic fibers PVA, PP, PE, and POM does not exceed 30%, and the impact height is (45 to 75 cm), the UHPC durable crack width impact times of different mixed fibers and impact heights can be calculated according to the following formula:

[0110]

[0111] Among them, b2 and c2 are coefficients related to fiber characteristic parameters.

[0112] b2=6.20-1.39λ sf -0.08λ pf (2)

[0113] c2=(5.35-3.85λ sf +13.46λ pf -15.41λ pf 2 +5.54λ pf 3 )·10 11 (3)

[0114] Where: Steel fiber characteristic parameter λ sf , Synthetic fiber (PVA, PP, PE, POM) characteristic parameters λ pf Calculate as follows:

[0115] λ sf =ρ sf l sf / d sf (4)

[0116] λ pf =ρ pf l pf / d pf (5)

[0117] In the above formula (2), ρ sf ,pf are the volumetric dosages of steel fiber and synthetic fiber, respectively, in percentage; l sf / d sf With l pf / d pf are the aspect ratios of steel fiber and synthetic fiber, respectively.

[0118] According to the relevant parameters of the mixed fiber UHPC and formula (1), the durable crack width impact number of the UHPC at an impact height of 50 cm is calculated, and the predicted impact fatigue life (years) is obtained by dividing it by 20.

[0119] II. The process of invention and creation

[0120] 1 Experimental Overview

[0121] 1.1 Raw materials

[0122] UHPC is composed of cement, silica fume, quartz powder, quartz sand, water, water reducing agent, steel fiber, synthetic fiber, etc. Cement is P·O52.5 ordinary Portland cement (OPC); silica fume (SF), light gray powder; quartz powder (QP), white powder; quartz sand (QS1) with 26-40 mesh (0.43-0.74mm) and quartz sand (QS2) with 70-120 mesh (0.13-0.18mm); mixing water is city tap water; water reducing agent is a powder high-performance polycarboxylate water reducing agent produced by a certain company, pure white powder; steel fiber is copper-plated straight steel fiber (SSF), and synthetic fibers include polyvinyl alcohol fiber (PVAF), polypropylene fiber (PPF), polyethylene fiber (PEF) and polyformaldehyde fiber (POMF).

[0123] The Hunan Changyong Expressway, which was opened to traffic in December 2003 and overhauled in December 2021, and the newly built Wuyi Expressway in September 2022, use C50 steel fiber concrete and C50 PP fiber concrete in the expansion joint anchorage area of ​​the bridge respectively. Except for the different fibers, both types of fiber concrete are composed of cement, river sand, crushed stone, water, and water reducer. The cement is P·O52.5 grade ordinary Portland cement; the river sand (river sand, RS) particle size range is 0~4.75mm; the crushed stone (crushed stone, CS) particle size range is 9.5~19mm; the water uses city tap water; the water reducer uses polycarboxylic acid water reducer; the steel fiber uses milling steel fiber (Milling steel fiber, MSF), and the PP fiber is abbreviated as PPF. The physical performance indicators of each fiber are shown in Table 1. The appearance of the fiber is as shown in Figure 3 .

[0124] Table 1 Physical properties of each fiber

[0125]

[0126] 1.2 Mix design, test parameters and grouping

[0127] The water-binder ratio of UHPC in this paper is mw / mb=0.18, the mass fraction of water reducer is 0.8%, and the mix ratio is m(OPC):m(SIF):m(QP):m(QS1):m(QS2)=1:0.33:0.13:0.77:0.43. The total volume content of fiber is set to 2%, and the control group is a single 2% steel fiber. Four kinds of synthetic fibers are used to replace part of the steel fibers in UHPC, and the volume replacement rates β are 10%, 20%, and 30%, respectively. The specimen numbers and parameters are shown in Table 2.

[0128] The water-cement ratio of steel fiber concrete (NC1) and PP fiber concrete (NC2) is 0.32, and the mix ratios are m(OPC):m(RS):m(CS):m(WSF)=1:1.33:2.27:0.16; m(OPC):m(RS):m(CS):m(PPF)=1:1.50:2.25:0.003 respectively.

[0129] Table 2 UHPC specimen number and fiber volume content

[0130]

[0131] Note: The plain UHPC group in the table refers to the UHPC without fiber addition in this article.

[0132] 1.3 Test methods

[0133] The preparation of UHPC materials adopts the process of dry mixing first and then wet mixing. During the preparation process, the raw materials (cement, silica fume, sand, and some powdered admixtures) are first dry mixed evenly (about 2 to 3 minutes), and then the evenly mixed water and admixtures are slowly added during the mixing process, and wet mixed (4 to 6 minutes). When the mixture enters the viscous flow state, steel fiber or synthetic fiber is evenly sprinkled in and continued to stir for 5 to 7 minutes. After that, the expansion test is carried out and the casting is carried out. Among them, those with an expansion of less than 650mm should be properly vibrated, and the mold is removed after curing at room temperature for 2 days, and then steam curing (95℃±5℃) for 2 days.

[0134] C50 fiber concrete is directly made by wet mixing process. After casting and forming, it is placed in a standard curing room (temperature (20℃±5℃), relative humidity ≥95%) for 28 days.

[0135] The expansion and slump tests were measured with slump cones and expansion plates in accordance with the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T20080-2016). The static mechanical properties test was carried out in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). The compression specimen was a 100mm×100mm×100mm cube; the tensile specimen was a dog bone specimen; the flexural specimen was a 100mm×100mm×400mm prism, and 3 specimens were tested in each group. The compressive strength test was conducted using a 3000kN electro-hydraulic servo universal testing machine with a loading rate of 0.8MPa / s; the tensile strength test was conducted using a CSDW-300M concrete ultimate tensile testing machine with a loading rate of 0.2mm / min; the flexural strength test was conducted using a 2000kN universal testing machine with a loading rate of 0.2mm / min.

[0136] The impact test was carried out with reference to the "Fiber Concrete Test Method" (CECS13:2009) and the concrete impact test method recommended by the American Concrete Institute (ACI544.2R-89) using a self-developed automatic impact test device. Figure 4As shown. The impact test piece is a Ф150mm×(63±2)mm cylinder, and 3 pieces are cast for each mix ratio. Before the test, the test piece is installed on the impact test device, and the test piece is clamped with a wooden strip to limit its lateral displacement, and then an impact steel ball with a diameter of 63mm is fixed in the middle of the top surface of the test piece. During the test, the impact hammer falls freely from a certain height and impacts the impact steel ball placed in the center of the top surface of the test piece. After each impact loading, the crack observation instrument is used to carefully check the cracking and damage of the test piece surface (top and bottom surfaces). When the first visible crack (0.02mm) appears on the test piece, the corresponding impact number is the initial crack impact number N1; after the initial crack, the limiting wooden strip is immediately removed, and the impact loading is continued until the main crack width reaches or exceeds 10mm, and the test ends. During this process, the crack width is tested at regular intervals. The impact number when the crack width of the specimen reaches 0.10mm or is closest to 0.10mm is defined as the durable crack width impact number N2; when the main crack width reaches 10mm, the specimen is destroyed, and the impact number at this time is the destruction impact number N3. N1, N2, and N3 are collectively referred to as characteristic impact numbers in this article. The impact energy dissipation of the specimen from the initial crack to the destruction is calculated according to formula (1); the impact ductility ratio μ of the specimen is calculated according to formula (2), which is used to reflect the ratio of the impact number from the initial crack to the destruction to the initial crack impact number; the toughness coefficient C is calculated according to formula (3), which is used to reflect the ratio of the anti-destruction impact energy dissipation of the specimen to the anti-destruction impact energy dissipation of the plain UHPC.

[0137] W i =N i mgh (1)

[0138] μ=(N3-N1) / N1 (2)

[0139] C=W3 / W 3-0 (3)

[0140] Wherein: i is only 1, 2, 3; Wi is the impact energy (J) - W1 is the impact energy to resist the initial crack, W2 is the impact energy to resist the durable crack width, and W3 is the impact energy to resist the destruction; Ni is the impact number; W3-0 is the impact energy to resist the destruction of the plain UHPC (J); m is the mass of the impact hammer, which is 4.5kg; g is the acceleration of gravity, which is 9.8N / kg; h is the impact height.

[0141] The 14 groups of specimens in Table 2 and the NC1 and NC2 specimens were subjected to impact tests at an impact height of 100 cm, and then three groups of specimens, SSF, PPF2, and PEF2, were selected to perform impact tests at impact heights of 50 cm and 75 cm, respectively, and NC1 and NC2 were selected to perform impact tests at an impact height of 50 cm.

[0142] 2 Test results of construction performance and basic mechanical properties of each mix ratio

[0143] 2.1 Construction performance

[0144] Table 3 shows the expansion, compressive strength, flexural strength and tensile strength results of steel fiber UHPC, hybrid fiber UHPC and C50 fiber concrete, as well as the compressive strength test results of plain UHPC (except for the absence of fiber, other proportions remain unchanged). Figure 5 The effect of synthetic fiber substitution on the expansion of UHPC. C50 fiber concrete is easier to mix and has better fluidity. Figure 5 It can be seen that with the increase of volume replacement rate, the expansion of UHPC after the four kinds of synthetic fibers are mixed separately shows a decreasing trend; and according to the degree of weakening of the material expansion, the four kinds of synthetic fibers are from large to small: PVA fiber>PE fiber>PP fiber>POM fiber. However, no obvious fiber agglomeration was observed during the casting process of all specimens, and those with an expansion of more than 500mm can basically self-level.

[0145] This is because compared to steel fibers, synthetic fibers have a larger specific surface area and a greater number of fibers in the same volume, requiring more cement slurry to wrap, thereby reducing the fluidity of UHPC

[23] . Among them, due to the presence of hydrophilic hydroxyl groups on the surface of PVA fibers, a large number of water molecules will be adsorbed on the fiber surface, reducing the free water in the mixture and further reducing its fluidity

[24] .

[0146] Table 3 Construction performance and basic mechanical properties of each mix ratio

[0147]

[0148] Note: Average in the table means average value, C v Represents the coefficient of variation.

[0149] 2.2 Basic mechanical properties

[0150] Figure 6 to Figure 8 The following are the effects of synthetic fiber substitution on the compressive strength, flexural strength and tensile strength of UHPC. It can be seen that with the increase of volume substitution rate, the compressive strength of hybrid fiber UHPC gradually decreases; the flexural strength first increases and then decreases, reaching the maximum value when the volume substitution rate is 20%; when mixed with PVA and PP fibers, the tensile strength first decreases and then increases, reaching the minimum value when the volume substitution rate is 20%, and increases at 30% but is still lower than the SSF specimen, while the tensile strength when mixed with PE and POM fibers gradually decreases. Some scholars have also obtained similar results [25,26].

[0151] It can be seen from Table 3 that although some mechanical properties of UHPC are slightly reduced after mixing with fibers, they are far better than those of C50 fiber concrete. The compressive strength and flexural strength of the NC1 and NC2 fiber concrete are only 68.2 MPa and 6.5 MPa, 61.8 MPa and 6.1 MPa, respectively.

[0152] 3 Test results and discussion of impact resistance of various mix ratios

[0153] 3.1 Impact resistance test results and discussion

[0154] Table 4 shows the test results of characteristic impact numbers of each mix ratio. In order to investigate the improvement of the impact resistance of UHPC of each mix ratio compared with C50 steel fiber concrete (service life of about 5 to 8 years) which has been tested for many years in real bridges, the ratio α of the characteristic impact number of each mix ratio to the corresponding characteristic impact number of C50 steel fiber (NC1) at each impact height is calculated from Table 4. i (i=1,2,3), the results are shown in Table 5.

[0155] Table 4 Impact test results of various mix ratios

[0156]

[0157]

[0158] Note: The data in brackets after the symbols of each ratio in the table are the impact heights. Example: SSF(100) refers to the impact test number of the SSF specimen at an impact height of 100 cm. The same applies below. Cv1, Cv1, Cv1 are the coefficients of variation corresponding to N1, N1, N1 respectively.

[0159] It can be seen from Tables 4 and 5 that: (1) Regardless of which synthetic fiber, PVA, PE, PP, or POM, replaces part of the steel fiber, when the total fiber volume content remains unchanged at 2%, the impact resistance (characteristic impact number) and toughness coefficient of the mixed fiber UHPC are the best when the synthetic fiber replacement rate is 10% (i.e., its volume content is 0.2%); after the synthetic fiber replacement rate exceeds 10%, as the replacement rate increases, the impact resistance decreases, and the PVA-steel fiber mixed fiber UHPC decreases slowly, while the mixed fiber UHPC of the other three synthetic fibers decreases rapidly, which fully demonstrates the importance of controlling the volume replacement rate of each synthetic fiber. (2) The ductility ratio of the mixed fiber UHPC of PVA, PP, and PE first increases and then decreases with the increase of the volume replacement rate, and is the largest at 10%. The ductility ratio of the mixed fiber UHPC of POM first decreases, then increases, and then decreases with the increase of the volume replacement rate, and is the smallest when the replacement rate is 10%, and the largest when it is 20%. (3) The characteristic impact numbers of steel fiber UHPC and each mixed fiber UHPC are 2.79 to 48.54 times the corresponding characteristic impact numbers of C50 steel fiber concrete, which are greatly improved, while the characteristic impact number of plain UHPC is only 0.18 to 0.47 times that of C50 steel fiber concrete. Therefore, it can be inferred that UHPC with a certain fiber content must have good impact resistance. (4) The impact resistance of mixed fiber UHPC with a synthetic fiber replacement rate of 10% (based on the durable crack width impact number as the judgment standard, because the steel fiber is prone to rust after the crack exceeds the durable crack width, the same below) is as follows: PP, PE, PVA, POM. At an impact height of 100 cm, the mixed fiber UHPC of the first three is 3.75 to 4.25 times that of steel fiber UHPC, and the mixed fiber UHPC of POM is 2.32 times that of steel fiber UHPC, which fully illustrates the importance of mixing. (5) For steel fiber UHPC and hybrid fiber UHPC with a synthetic fiber replacement rate of 20%, the increase multiple of the characteristic impact number increases with the decrease of impact height. The increase ratio of the characteristic impact coefficient of the durable crack width when the impact height decreases from 100 cm to 50 cm is 23.4% (i.e. (14.07-11.40) / 11.40, the same below) to 44.3%. It can be inferred that the hybrid fiber UHPC with a synthetic fiber replacement rate of no more than 20% shows the same rule. (6) Although the impact resistance of NC2 (C50 PP fiber concrete) at an impact height of 100 cm is comparable to or even better than that of NC1 (C50 steel fiber concrete), the impact resistance at an impact height of 50 cm is much lower than that of NC1. Considering that the number at an impact height of 50 cm is much higher than the corresponding number at an impact height of 100 cm, it can be considered that the above results are due to the fact that the fatigue resistance of PP fibers in the concrete matrix is ​​far inferior to that of steel fibers.

[0160] Considering that: the number of wheel actions experienced by the anchorage area under the wheel track line of the expansion joint of the highway bridge in 5 years is much greater than the number of characteristic impacts corresponding to NC1(50) in Table 4; the impact height of 50 cm is the minimum height of the standard impact test (the minimum is 457 mm

[27] , and the number of impact tests with a smaller height is too large, which is too much work); the number of characteristic impacts in the standard impact test decreases with the increase of the impact height, and the reduction law varies depending on the composition of the specimen material; after the crack exceeds the durable crack width, the steel fiber is prone to failure due to corrosion, etc. Therefore, it is recommended to use the durable crack width impact number of the standard impact test with an impact height of 50 cm to characterize the relative size of the impact resistance of the concrete in the anchorage area of ​​the expansion joint.

[0161] According to the impact number of the durable crack width of the standard impact test with an impact height of 50 cm, the increase ratio of the characteristic impact coefficient of the durable crack width when the impact height is reduced from 100 cm to 50 cm is at least 23.4%, and the data in Table 5, it can be obtained that the impact resistance of the mixed fiber UHPC and steel fiber UHPC with a replacement rate of 10% for PP, PE, PVA, and POM is about 59.9, 53.7, 52.8, 32.7, and 14.1 times that of C50 steel fiber. The life of C50 steel fiber concrete in the anchorage area of ​​the expansion joint of the bridge is slightly conservatively calculated as 5 years. The life of the mixed fiber UHPC in the anchorage area of ​​the expansion joint of the bridge mentioned above will reach 163.5 to 299.5 years, the life of the steel fiber UHPC will reach 70.35 years, and the life of the C50 PP fiber concrete will be 2.6 years.

[0162] Table 5 Ratio of characteristic impact number of each mix ratio to the corresponding characteristic impact number of NC1 at two impact heights α i (i=1,2,3)

[0163]

[0164] Fig. 9 , Fig.10 The relationship between the maximum crack width and the impact number of steel fiber UHPC, hybrid fiber UHPC and two C50 fiber concretes at impact heights of 100 cm and 50 cm is given. It can be seen that when the crack width is less than 0.5 mm, the crack width of all UHPC specimens increases slowly with the increase of the impact number, and when the crack width is greater than 1.0 mm, it increases rapidly with the impact number; when the impact height decreases from 100 cm to 50 cm, the growth rate of the crack width with the impact number decreases significantly; the growth rate of the crack width of C50 fiber concrete with the impact number is much greater than that of hybrid fiber UHPC.

[0165] This further illustrates the excellent impact resistance of UHPC and the rationality of using the durable crack width impact number of the standard impact test with an impact height of 50 cm to characterize the impact resistance of the expansion joint anchorage area. After exceeding the durable crack width, if the steel wire corrosion is not considered, there is still a long impact resistance life reserve.

[0166] 3.2 Hybrid fiber reinforcement mechanism

[0167] The first crack impact number of UHPC after fiber mixing shows a trend of "first increasing and then decreasing" with the increase of volume replacement rate, and reaches the maximum value when the volume replacement rate is 10%. This is because: during the mixing process, synthetic fibers and steel fibers form a network structure, which can effectively restrict the initiation and development of cracks

[29] ; at the same time, synthetic fibers are small in size and large in number, which can play a good crack-blocking effect in the impact crack generation stage, passivate the stress concentration at the tip of microcracks, and hinder the development of microcracks

[30] . However, excessive synthetic fiber replacement will also reduce the fluidity of UHPC, resulting in reduced fiber dispersion uniformity, thereby forming a weak surface

[28] . Therefore, when the volume replacement rate increases to 20% and 30%, the first crack impact number of hybrid fiber UHPC gradually decreases.

[0168] As the impact load continues, the specimen shows multiple cracks, and eventually forms a main crack until it is destroyed. Fig. 9 It can be seen that in the crack development stage, compared with the SSF group, except for the slightly weaker toughening effect of the specimens mixed with PP fibers, the other three types of polymer synthetic fibers delayed the development of cracks after being mixed, showing a good toughening effect.

[0169] It can be seen that there is also a good synergistic effect between the synthetic fiber and the steel fiber after the specimen cracks. This is because: when the macro crack width is small, the steel fiber has a strong crack blocking effect at the initial loading stage due to its large elastic modulus, high strength, and bonding force and "mechanical bite force" with the UHPC matrix [29,31]; and as the impact load continues, the crack width gradually increases. After some steel fibers are pulled out, the synthetic fiber with a smaller elastic modulus begins to act as the main force to block the crack until it is also pulled out or broken

[32] . The two work together to exert the effect of crack blocking and toughening, effectively improving the impact resistance of the specimen.

[0170] 4 Calculation formula of UHPC characteristic impact number based on impact height and fiber characteristic parameters

[0171] For the same UHPC matrix material, if the characteristic impact number can be expressed as a function of fiber type, dosage and impact height, the impact resistance of UHPC can be predicted more conveniently, which is of great significance for the selection of fiber type and dosage in structural parts with impact performance requirements such as bridge expansion joint anchorage areas.

[0172] Preliminary analysis shows that for the same UHPC matrix material, the impact resistance of mixed fiber UHPC is mainly related to the characteristic parameters of steel fibers and synthetic fibers. The different effects of synthetic fibers (PVA, PP, PE, POM) on impact resistance are mainly reflected in the differences in fiber characteristic parameters, rather than in material properties. In order to quantify the effect of fiber on impact resistance, the steel fiber characteristic parameter λ is introduced. sf , Synthetic fiber characteristic parameter λ pf :

[0173] λ sf =ρ sf l sf / d sf (4)

[0174] λ pf =ρ pf l pf / d pf (5)

[0175] Where: sf , pf are the volumetric dosages of steel fiber and synthetic fiber, respectively, in percentage; l sf / d sf With l pf / d pf are the aspect ratios of steel fiber and synthetic fiber, respectively.

[0176] The UHPC impact data in Table 4 were statistically analyzed, and the relationship between the durable crack width impact number N2 and the single impact height H was:

[0177]

[0178] Among them, b2 and c2 are coefficients related to the fiber characteristic parameters. Based on the fitting analysis of the test results of the UHPC (containing steel fiber and four kinds of mixed fibers) specimens in this paper, their expressions are:

[0179] b2=6.20-1.39λ sf -0.08λ pf (7)

[0180] c2=(5.35-3.85λ sf +13.46λ pf -15.41λ pf 2 +5.54λ pf 3 )·10 11 (8)

[0181] The calculation value of the endurance crack width impact number N2 fitting formula and the test value are shown in Table 6. Fig.11. Among them, the goodness of fit R2 of the N2 formula is 0.999, the average value of the ratio of the calculated value to the test value is 0.986, and the coefficient of variation is 21.18%. Among them, when the impact height is 100cm, the average value of the ratio of the calculated value to the test value is 0.961, and the coefficient of variation is 25.97%; when the impact height is 75cm, the average value of the ratio of the calculated value to the test value is 1.078, and the coefficient of variation is 3.43%. When the impact height is 50cm, the average value of the ratio of the calculated value to the test value is 0.999, and the coefficient of variation is 0.15%. As the impact height decreases, the prediction accuracy of formula (6) is better, and it can be inferred that when the impact height does not exceed 50cm, the prediction accuracy of formula (6) is high and fully meets the engineering needs. In fact, when the impact height is higher and the number of impacts is smaller, the discreteness of the impact number of the durable crack width of different UHPC specimens with the same impact height and the same ratio is also greater.

[0182] Since formulas (6) to (8) are based on the impact test data of UHPC specimens in which the total fiber content is 2%, four synthetic fibers, PVA, PP, PE, and POM, are mixed with steel fibers respectively, and the substitution rate does not exceed 30%, it is worth further study whether the applicable range can be expanded or to what extent it can be expanded.

[0183] Table 6 N2 calculated value and test value results

[0184]

[0185] Note: r is the ratio of the calculated value of the characteristic impact number to the test value.

[0186] 5 Conclusion

[0187] (1) Based on the service life of concrete in the anchorage area of ​​bridge expansion joints and the corrosion conditions of steel wire in concrete, the concept of durable crack width impact number was proposed; based on the result that the durable crack width impact number of C50 steel fiber concrete at an impact height of 50 cm is much smaller than the number of times the bridge expansion joints are subjected to wheel action during their service life, and the fact that the minimum impact height of the standard impact test is 47.5 cm and is very close to 50 cm, and the test workload (number of impacts) should not be too large, a reasonable method for characterizing the impact resistance of concrete in the anchorage area of ​​expansion joints was proposed - using the durable crack width impact number at an impact height of 50 cm in the standard impact test.

[0188] (2) Regardless of which synthetic fiber, PVA, PE, PP, or POM, replaces part of the steel fiber, the total fiber content remains unchanged at 2%, and the characteristic impact number and toughness coefficient of the mixed fiber UHPC are the largest when the synthetic fiber substitution rate is 10% (i.e., the dosage is 0.2%); when the synthetic fiber substitution rate exceeds 10%, as the substitution rate increases, the impact resistance of the PVA mixed fiber UHPC decreases slowly, while the other three mixed fiber UHPC decreases rapidly, which shows the importance of controlling the substitution rate of each synthetic fiber.

[0189] (3) When the crack width is less than 0.5 mm, the crack width of all UHPC specimens increases slowly with the increase of the impact number. When the crack width is greater than 1.0 mm, it increases rapidly with the impact number. When the impact height is 50 cm, the growth rate of the crack width with the impact number is significantly lower than that when the impact height is 100 cm. The growth rate of the crack width of C50 fiber concrete with the impact number is much greater than that of hybrid fiber UHPC.

[0190] (4) According to the proposed characterization method of the impact resistance of the expansion joint anchorage area, the life of the C50 steel fiber concrete bridge expansion joint anchorage area is 5 years, and the life of the bridge expansion joint anchorage area of ​​the mixed fiber UHPC with a replacement rate of 10% for PP, PE, PVA, and POM is 299.5, 268.5, 264.0, and 163.5 years, respectively, and the life of the steel fiber UHPC and C50 PP fiber concrete is 70.4 and 2.6 years, respectively. According to the inference, the actual life of the first five is longer than the aforementioned, and the actual life of the latter is shorter than the aforementioned.

[0191] (5) The calculation formulas for the initial crack impact number N1, the durable crack width impact number N2 and the destruction impact number N3 of UHPC based on the fiber characteristic parameters and the impact height were proposed. When the total fiber content was 2%, the substitution rate of the four synthetic fibers, PVA, PP, PE and POM, did not exceed 30%, and the impact height was not greater than 75 cm, the prediction accuracy was high enough to meet the engineering accuracy requirements. However, the prediction accuracy decreased rapidly with the increase of the impact height.

[0192] The following are two specific examples of characterization methods for the impact fatigue performance of the anchor body of the bridge expansion device and reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC (ultra-high performance concrete):

[0193] Embodiment 1:

[0194] 1. Experimental testing and characterization of impact life determination of cement-based composite anchors in bridge expansion joints:

[0195] Prepare standard-sized bridge expansion joint cement-based composite anchor specimens.

[0196] The impact resistance of the samples was tested using an impact fatigue testing machine, and the damage of the samples after each impact was recorded.

[0197] Based on the test data, the impact resistance life of the anchor body is analyzed and determined by statistical methods.

[0198] 2. Reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC:

[0199] The total fiber volume content was set at 2% to ensure uniform distribution of fibers in UHPC.

[0200] Synthetic fibers (such as PVA, PP, PE, POM) are selected to replace part of the steel fibers, and the replacement rate is set to 10%.

[0201] The steel fiber length was selected to be 12 mm, and the aspect ratio was set to 80 to ensure good bonding between the fiber and the matrix.

[0202] The fiber lengths of PVA, PP, PE, and POM are all 12 mm. The aspect ratios of the first three are set to 400, and the aspect ratio of POM is set to 80.

[0203] The aggregate diameter of UHPC is strictly controlled within 3mm to ensure the uniformity and strength of the concrete.

[0204] The compressive strength of UHPC should be no less than 120MPa, and the tensile strength should be no less than 7MPa to meet actual engineering needs.

[0205] Embodiment 2:

[0206] 1. Experimental testing and characterization of impact resistance life determination of cement-based composite anchors for bridge expansion joints (same as in Example 1).

[0207] 2. Reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC:

[0208] The total fiber volume content is set at 2.5% to obtain better reinforcement effect.

[0209] The substitution rate of synthetic fibers (PVA, PP, PE, POM) for steel fibers is set at 14% to achieve complementary advantages of the fibers.

[0210] The steel fiber length was selected to be 16 mm, and the aspect ratio was set to 100 to improve the pull-out resistance and crack resistance of the fiber.

[0211] The fiber lengths of PVA, PP, PE, and POM are all 14 mm. The aspect ratios of the first three are set to 500, and the aspect ratio of POM is set to 100.

[0212] The aggregate diameter of UHPC is controlled within 2.5mm to further improve the density and strength of concrete.

[0213] The compressive strength of UHPC should be no less than 130MPa, and the tensile strength should be no less than 8MPa to meet higher requirements of engineering applications.

[0214] The present invention also provides an impact fatigue performance characterization system for an anchor body of a bridge expansion device, the system comprising:

[0215] An impact life determination module for experimental testing and characterization of the impact life of cement-based composite anchors in bridge expansion joints;

[0216] A key parameter value module is used to determine the reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC, including total fiber volume content, synthetic fiber substitution rate, fiber length, aspect ratio, UHPC aggregate diameter, UHPC compressive strength and tensile strength;

[0217] An impact durability life prediction module is used to predict the impact durability life of impact-resistant hybrid fiber UHPC based on its key parameters.

[0218] The key parameter value module further includes:

[0219] The fiber volume total dosage setting unit is set to 2%±0.5%;

[0220] Synthetic fiber substitution rate setting unit, set to 8% to 16%;

[0221] The fiber length and aspect ratio setting unit sets the steel fiber length to 8mm-16mm and the aspect ratio to 60-100. The lengths of PVA, PP, PE and POM are all about 10-14mm. The aspect ratios of the first three are 300-500, and the aspect ratio of the latter is 60-100.

[0222] The UHPC parameter setting unit sets the aggregate diameter of UHPC to no more than 3 mm, the compressive strength of UHPC to no less than 120 MPa, and the tensile strength to no less than 7 MPa.

[0223] Impact durability life prediction module includes:

[0224] The impact durability crack width impact number calculation unit calculates the UHPC durability crack width impact number of different mixed fibers and impact heights through a preset formula based on the given total fiber amount, synthetic fiber substitution rate and impact height;

[0225] The impact fatigue life prediction unit divides the calculated number of durable crack width impacts by a preset coefficient (such as 20) to predict the impact fatigue life.

[0226] The impact durability crack width impact number calculation unit further includes:

[0227] The fiber characteristic parameter calculation subunit is used to calculate the fiber characteristic parameters according to the volume content and aspect ratio of the steel fiber and the synthetic fiber;

[0228] The impact durable crack width impact number calculation subunit is used to substitute the calculated fiber characteristic parameters into a preset formula to calculate the durable crack width impact number.

[0229] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A bridge expansion device anchor body and impact fatigue performance characterization method, characterized in that: The following steps are involved: Step 1, experimental testing and characterization of impact life determination of cement-based composite anchors of bridge expansion joints; Step 2, reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC; Step 3, impact durability life prediction formula of impact-resistant hybrid fiber UHPC; The impact durability life prediction formula of the impact-resistant hybrid fiber UHPC is: When the total fiber volume content is 2% ± 0.5%, the substitution rate of the four synthetic fibers of PVA, PP, PE and POM does not exceed 30%, and the impact height is 45-75cm, the impact times of the UHPC durable crack width with different mixed fibers and impact heights can be calculated according to the following formula: Among them, b2 and c2 are coefficients related to fiber characteristic parameters, N2 is the number of impacts of durable crack width, and H is the impact height; b2=6.20-1.39λ sf -0.08λ pf (2) c2=(5.35-3.85λ sf +13.46m pf -15.41m pf 2 +5.54m pf 3 )·10 11 (3) Where: Steel fiber characteristic parameter λ sf , Synthetic fiber PVA, PP, PE, POM characteristic parameters λ pf Calculate as follows: l sf =ρ sf l sf / d sf (4) l pf =ρ pf l pf / d pf (5) In the above formula (2), ρ sf , pf are the volumetric dosages of steel fiber and synthetic fiber, respectively, in percentage; l sf / d sf With l pf / d pf are the aspect ratios of steel fiber and synthetic fiber respectively; According to the relevant parameters of the mixed fiber UHPC and formula (1), the number of impacts of the durable crack width of the UHPC at an impact height of 50 cm is calculated, and the predicted impact fatigue life is obtained by dividing it by 20; The reasonable value determination method of the key parameters of the impact-resistant hybrid fiber UHPC is as follows: The key parameters of the impact-resistant hybrid fiber UHPC of the anchor body of the bridge expansion device include: the total fiber volume dosage is 2%±0.5%; the replacement rate of synthetic fibers for steel fibers is 8%~16%, and the synthetic fibers include polyvinyl alcohol fibers PVA, polypropylene fibers PP, polyethylene fibers PE, and polyoxymethylene fibers POM; the length of steel fibers is 8mm~16mm, and the aspect ratio is 60~100; the length of PVA, PP, PE, and POM are all 10~14mm, the aspect ratio of the former three is 300~500, and the aspect ratio of the latter is 60~100, the aggregate diameter of UHPC does not exceed 3mm, the compressive strength of UHPC is not less than 120MPa, and the tensile strength is not less than 7MPa.

2. A bridge expansion device anchor body and impact fatigue performance characterization system implementing the bridge expansion device anchor body and impact fatigue performance characterization method as claimed in claim 1, characterized in that: include: An impact life determination module for experimental testing and characterization of the impact life of cement-based composite anchors in bridge expansion joints; A key parameter value module is used to determine the reasonable values ​​of key parameters of impact-resistant hybrid fiber UHPC, including total fiber volume content, synthetic fiber substitution rate, fiber length, aspect ratio, UHPC aggregate diameter, UHPC compressive strength and tensile strength; An impact durability life prediction module is used to predict the impact durability life of impact-resistant hybrid fiber UHPC based on its key parameters.

3. The bridge expansion device anchor body and impact fatigue performance characterization system according to claim 2, characterized in that: The key parameter value acquisition module further includes: The fiber volume total dosage setting unit is set to 2%±0.5%; Synthetic fiber substitution rate setting unit, the synthetic fiber substitution rate is set to 8% to 16%; The fiber length and aspect ratio setting unit sets the steel fiber length to 8mm-16mm and the aspect ratio to 60-100. The lengths of PVA, PP, PE and POM are all 10-14mm. The aspect ratios of the first three are 300-500, and the aspect ratio of the latter is 60-100. The UHPC parameter setting unit sets the aggregate diameter of UHPC to no more than 3 mm, the compressive strength of UHPC to no less than 120 MPa, and the tensile strength to no less than 7 MPa.

4. The bridge expansion device anchor body and impact fatigue performance characterization system according to claim 2, characterized in that: The impact durability life prediction module includes: The impact durability crack width impact number calculation unit calculates the UHPC durability crack width impact number of different mixed fibers and impact heights through a preset formula based on the given total fiber volume content, synthetic fiber substitution rate and impact height; The impact fatigue life prediction unit divides the calculated endurance crack width impact times by a preset coefficient to predict the impact fatigue life.

5. The bridge expansion device anchor body and impact fatigue performance characterization system according to claim 4, characterized in that: The impact durability crack width impact number calculation unit further includes: The fiber characteristic parameter calculation subunit is used to calculate the fiber characteristic parameters according to the volume content and aspect ratio of the steel fiber and the synthetic fiber; The impact durable crack width impact number calculation subunit is used to substitute the calculated fiber characteristic parameters into a preset formula to calculate the durable crack width impact number.

6. A computer device, characterized in that: The computer device includes a memory and a processor, the memory stores a computer program, and when the computer program is executed by the processor, the processor executes the steps of the method for characterizing the anchor body and impact fatigue performance of the bridge expansion device as claimed in claim 1.

7. A computer-readable storage medium storing a computer program, wherein when the computer program is executed by a processor, the processor executes the steps of the method for characterizing the anchor body and impact fatigue performance of a bridge expansion device as described in claim 1.

8. An information data processing terminal, characterized in that: The information data processing terminal is used to implement the bridge expansion device anchor body and impact fatigue performance characterization system as described in claim 2.